2011
DOI: 10.1016/j.flora.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intraplant variation in nectar traits in Helleborus foetidus (Ranunculaceae) as related to floral phase, environmental conditions and pollinator exposure

Abstract: a b s t r a c tFactors that contribute to variation in nectar sugar composition, nectar concentration and volume have been a central concern in studies of pollinator assemblages in angiosperms. In an effort to better understand the mechanisms underlying variation in nectar traits, we designed a series of experiments with flowering Helleborus foetidus individuals under natural and glasshouse conditions, to identify intraplant variation in nectar traits which depend on both intrinsic (sexual phases of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Despite being conducted in different years and with differences in design, length of exposure time to pollinators, and type of nectar involved (natural vs. artificial), the two field experiments consistently demonstrated that flowers with nectaries containing M. reukaufii populations had their nectar most thoroughly depleted by bumble bees. Because all nectaries were similarly filled with nectar at the beginning of the exposure period, and nectaries with and without yeasts secrete nectar at similar rates (Canto et al 2011), the most parsimonious explanation for yeast-related differences in residual amount of nectar is that bumble bee foragers discriminated between flower types and preferred nectar with M. reukaufii. Rigorously testing this interpretation would require direct observations of insect visits to treated and control flowers, but unfortunately this possibility was precluded by the extraordinarily low pollinator visitation rates to H. foetidus flowers (Herrera et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being conducted in different years and with differences in design, length of exposure time to pollinators, and type of nectar involved (natural vs. artificial), the two field experiments consistently demonstrated that flowers with nectaries containing M. reukaufii populations had their nectar most thoroughly depleted by bumble bees. Because all nectaries were similarly filled with nectar at the beginning of the exposure period, and nectaries with and without yeasts secrete nectar at similar rates (Canto et al 2011), the most parsimonious explanation for yeast-related differences in residual amount of nectar is that bumble bee foragers discriminated between flower types and preferred nectar with M. reukaufii. Rigorously testing this interpretation would require direct observations of insect visits to treated and control flowers, but unfortunately this possibility was precluded by the extraordinarily low pollinator visitation rates to H. foetidus flowers (Herrera et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Captive and wild bumble bees in our study thus could have relied for yeast detection on some cue correlated with presence of yeasts in nectar, such as increased temperature, volatile emissions, yeast metabolites (e.g., ethanol), taste alterations, or sugar and amino acids profiles , Canto et al 2011). At present, we can only speculate about the sensory mechanism(s) involved in yeast detection by bumble bees, and their elucidation will require additional experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, H. foetidus ๙ectar imposes harsh co๙ditio๙s for microbial growth because of the high sugar co๙ce๙tratio๙ a๙d prese๙ce of a๙timicrobial substa๙ces (Herrera & al., 2006;Ca๙to & al., 2011). U๙der such co๙ditio๙s M. reukaufii usually reaches co๙siderably higher cell de๙sities tha๙ M. gruessii.…”
Section: Discussionmentioning
confidence: 99%
“…Each ๙ec-tary produces o๙ average 2 µL of ๙ectar which has high sugar co๙ce๙tratio๙s, with a๙ overall value of 59.7±19.4 g 100 mL −1 . Nectar is sucrose-domi๙ated (98.5%) with low perce๙tages of glucose (0.2%) a๙d fructose (1.3%; Ca๙to & al., 2011).…”
Section: Study Site and Nectar Sourcementioning
confidence: 99%
“…About half of the samples analyzed in a survey study were positive for yeast, which are responsible for alcoholic fermentation and thus modification of sugar composition [4]. Fermentation changes the sugar profile by reducing the total sugar concentration and lowering the level of sucrose [4,5]. This profound change in the chemistry of nectar may affect the plant-pollinator relationship since the sugar profile of nectar is strictly related to pollinator preferences [6,7].…”
Section: Introductionmentioning
confidence: 99%